Residual strength estimation and damage characterization by acoustic emission of drilled thermally conditioned fiberglass laminates - Kakkassery Joseph J.; Arumugam V.; Saravanakumar K.; Durga S.; Santulli C.; Pavlović A. (FME Transactions, 2018)
Structural components of composite materials in aerospace industries are assembled using fasteners, installed by performing cutting processes, such as drilling, on the material. In composites, this is considered particularly critical, because delamination due to mechanical stresses and fiber/resin pullout may be facilitated during cutting, so that the structural integrity of composite laminates may be affected. Acoustic emission (AE) technique is employed to monitor the failure modes and damage mechanism of drilled composite materials, while in an attempt to improve the strength of the composites, thermal conditioning has been applied. This paper investigates the residual performance of drilled unidirectional glass fiber reinforced plastic (GFRP) laminates subjected to various thermal conditioning methods. Thermally treated laminates underwent three-point flexural tests under AE monitoring to compare their residual strength with the untreated ones. The results clearly show that the thermal conditioning could be used as an effective method for minimizing delamination in GFRPs.